Spatial Modeling of Agricultural Carbon Footprints: Assessing Greenhouse Gas Emissions Based on Livestock Population and National NPK Fertilizer Consumption - Saida; Pieter J. Kunu; Andi Apriany Fatmawaty (CV. HEI PUBLISHING INDONESIA, 2026)
This study addresses the critical challenge of balancing national food security with climate mitigation by developing a spatial model of Indonesia's agricultural carbon footprint. Amid global Net Zero Emissions efforts, it identifies geographical